PROPOSAL FOR IMPROVEMENTS IN THE MONITORING OF CORRECTIVE ACTIONS IN SIMULTANEOUS CONTROL REPORTS. CASE: HUALLAGA PROVINCE, SAN MARTÍN, PERU 2021. - Hinostroza Mariño, Jhordan (2025)
General objective: To improve the adoption of measures to prevent and correct adverse events detailed in the reports under the simultaneous control modality carried out by organic units of the Supreme Audit Entity - SAI of Peru (COMPTROLLER’S OFFICE) to the Provincial Municipality of Huallaga and its districts, through the improvement proposal for its proper  implementation, taking into account the level of knowledge, monitoring and limitations for its proper implementation by the Entity’s workers. Methodology: The study is descriptive, with a mixed approach, descriptive theoretical method, the innovation value map of the Global Methodology 5F (EMOI Model) and the 5W2H methodology were used for the planning of the innovation challenge, historical information was used and surveys and interviews were applied. Results: Officials do not know the deadline to send the Action Plan of the communicated simultaneous control reports to the Institutional Control Body of the Provincial Municipality of Huallaga; Likewise, they are unaware of the maximum timeframe for implementing the reported events. Conclusions: The officials responsible for the Provincial Municipality of Huallaga lack knowledge regarding the timely monitoring and implementation of the adverse events detailed in the simultaneous reports. Keywords: Simultaneous control, adverse situation, improvement proposal, value creation, corrective measures, preventive measures, EMOI model and 5W2H Methodology.